2015
DOI: 10.1002/bem.21915
|View full text |Cite
|
Sign up to set email alerts
|

Circadian gene expression and extremely low‐frequency magnetic fields: An in vitro study

Abstract: It is well known that circadian clocks are mainly regulated by light targeting signaling pathways in the hypothalamic suprachiasmatic nucleus. However, an entrainment mediated by non-photic sensory stimuli was also suggested for peripheral clocks. Exposure to extremely low frequency (ELF) electromagnetic fields might affect circadian rhythmicity. The goal of this research was to investigate effects of ELF magnetic fields (ELF-MF) on circadian clock genes in a human fibroblast cell line. We found that an ELF-MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 55 publications
1
30
1
Order By: Relevance
“…The impact of (electro)magnetic fields on the circadian clock has been investigated by focusing in particular on the protein form of CRYPTOCHROME and its involvement in geomagnetic compass orientation (Gegear et al 2008;Yoshii et al 2009;Ritz et al 2010;Niessner et al 2013;Qin et al 2016;Sheppard et al 2017) or on clock output markers such as melatonin, cortisol or sleep (Lewczuk et al 2014), while the effects on the transcriptional clock itself, especially at the level of mRNA, are largely unknown. In a study on human fibroblasts, the influence of extremely low-frequency (ELF) electromagnetic fields (0.1 mT, 50 Hz) on the circadian genes BMAL1, PER2, PER3, CRY1 and CRY2 was addressed (Manzella et al 2015). The authors showed that the ELF-MF was able to entrain the transcriptional clock of serum-starved cells which lack a circadian oscillation and that also a previously entrained transcriptional clock was altered by the applied MF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of (electro)magnetic fields on the circadian clock has been investigated by focusing in particular on the protein form of CRYPTOCHROME and its involvement in geomagnetic compass orientation (Gegear et al 2008;Yoshii et al 2009;Ritz et al 2010;Niessner et al 2013;Qin et al 2016;Sheppard et al 2017) or on clock output markers such as melatonin, cortisol or sleep (Lewczuk et al 2014), while the effects on the transcriptional clock itself, especially at the level of mRNA, are largely unknown. In a study on human fibroblasts, the influence of extremely low-frequency (ELF) electromagnetic fields (0.1 mT, 50 Hz) on the circadian genes BMAL1, PER2, PER3, CRY1 and CRY2 was addressed (Manzella et al 2015). The authors showed that the ELF-MF was able to entrain the transcriptional clock of serum-starved cells which lack a circadian oscillation and that also a previously entrained transcriptional clock was altered by the applied MF.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of (electro)magnetic fields on the circadian clock has been addressed repeatedly (Vanderstraeten et al 2012(Vanderstraeten et al , 2015Manzella et al 2015;Vanderstraeten 2017), knowing that the light-dependent magnetosensitivity of animals is based on CRYPTOCHROME, a key protein of the circadian clock (Gegear et al 2008;Yoshii et al 2009;Ritz et al 2010;Niessner et al 2013;Qin et al 2016;Sheppard et al 2017). In this context, it is widely accepted that the functional mechanism for magnetic compass orientation in insects, birds, amphibians, reptiles, fish and mammals (Wiltschko and Wiltschko 2006) is assigned to the protein form of CRY which responds to alterations of the geomagnetic field by forming spin-correlated radical pairs (RPs) between FADH and three specific tryptophan residues, involving thus the cellular redox balance (Hore and Mouritsen 2016;Vanderstraeten 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The investigators also discussed the possible effects of magnetic flux on melatonin and circadian rhythms. In recent studies, it has been shown that weak EMFs can disturb melatonin secretion and circadian rhythms (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Among the various proposed mechanisms, the influence of ELF-MFs on DNA via gene expression is a challenge to test. The interaction could be direct, e.g., DNA can act as fractal antennae (Blank and Goodman, 2011b), or indirect, e.g., free radicals, the circadian clock, or calcium-related pathways can participate in the response (Sztafrowski et al, 2011; Manzella et al, 2015). The influence of ELF-MFs on gene transcription could be mediated by specific sequences, which were found in promoter regions in animals.…”
Section: Introductionmentioning
confidence: 99%